TRANSPARANSI DAN KEMUDAHAN AKSES DALAM PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KOLAKA - Taufik Taufik (Journal Publicuho, 2021)
This article aims to discuss the dimension of transparency in the process of organizing public services at the Office of Investment and Integrated Services One Door Kolaka Regency. The lack of access from citizens, limited public service information, and various maladministrations that occurred showed not an optimal improvement in the quality of public services in Indonesia. The idea of transparency in public services is that the government should be open with the availability of clear information and provide convenience to citizens in accessing services. this research uses a qualitative approach with a case study. Data is collected through interviews, observations, and documentation. The results of this study show that the process of organizing public services at the Office of Investment and Integrated Services One Door Kolaka Regency has been carried out transparently. Service executors have been open and provide all public service information needed by the community. Access to services can be reached easily by residents. Although some people have difficulty in accessing services online, the implementing officers always help and provide convenience as a form of responsiveness in public services.